Increasing The Social Equity by Implementing a Proper Methodology of Statistical Life Valuation - Frantz Daniel FISTUNG; Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA (Communications of International Proceedings, 2023)
This paper aims to propose an appropriate method for the monetary evaluation of statistical life (VSL) that could be used to obtain a unique value of that indicator for each individual in the world. In fact, all the analysis in this field must start from the idea that people are equal in the world, without taking into account the economic or social differences existing on the planet. Theoretically, the statistical value of a life (VSL) is the local rate of compromise between the risk of fatality and money. Over the past four or five decades, many researchers have tried to propose a better methodology for VSL evaluation. But, unfortunately, in these steps one of the most important premises was gradually eliminated. It was this that underscores that every human being on that planet must have the same economic significance/size. In other words, we all have to have the same VSL, without considering other influences (place of birth, economic or social conditions, gender, and so on). Therefore, the approach in this studio is different from those existing at the moment, as it proposes to link the value of statistical life over longer periods of time and for larger areas of analysis (regions, continents or even globally) by means of major economic indicators: gross domestic product per capita and life expectancy. Comparing the results achieved using the new formulas proposed in this paper, with others obtained using different methodologies and carried out internationally, in particular in the EU, for the period 2010-2021, the differences are not significant. In fact, there is a difference of less than 2% between the values obtained by these comparisons. The proposed method is more relevant and creates, as we have already pointed out, the possibility of adopting a single value for the value of global statistical life.
Keywords: Life expectancy; Monetary valuation method; Value of statistical life